AN ANALYSIS ON THE CONTENT VALIDITY OF ENGLISH SUMMATIVE TEST FOR THE SECOND GRADE IN THE FIRST TERM OF SMAN 6 JAKARTA IN 2013/2014 ACADEMIC YEAR - Apriyanti, Fitri (Fakultas Ilmu Pendidikan (FIP) Universitas Hasyim Asy'ari (Unhasy) Tebuireng Jombang, 2018)
Abstract This research is intended to know the content validity of English summative test of the first term for the second grade students of SMAN 6 Jakarta in 2013/2014 academic year. The research method used to know the content validity of English summative test for senior high school is descriptive comparative analysis method by analyzing and comparing the content of the English summative test to the content of KTSP (school based curriculum) for senior high school.